Hellenic coinage : the Alpha Bank collection - Τσαγκάρη, Δήμητρα, 1971- (Alpha Bank, 2007)
The Exhibition "Hellenic Coinage" possesses a curious contemporary relevance: it comes as a reminder that just as economic issues lie at the centre of present-day public concern in Greece, Europe and throughout the world, so 'the magnitudes of everyday problems were, are and will be primarily of an economic order'-as a wise igth century thinker expressed it. Moreover, it exemplifies how the factors of place and time interact to produce any historical phenomenon. Above all, however, the exhibition steadily transmits a salutary message from the past to the present and to the future concerning the crucial role of the economy in the struggle for survival and, indeed, in the concomitant spiritual struggles. The 500 ancient Greek coins, selected from among the some 10,000 in the Alpha Bank Collection, present in the most vivid manner the ideological underpinnings of the successive changes in the ancient Greek world: its history and geography, its thought, art and life. They constitute invaluable witnesses to the texture and temperament of a lost age, providing connecting links forthe reconstruction of the severed chain of continuity, while at the same time being instructive, thought-provoking and delightful to the eye. It is consequently not without reason that they have attracted the attention and interest of a bank and thanks to Alpha Bank's commitment to collect and conserve these coins, a further important body of evidence for Greek civilisation has been secured. Warm thanks are due to the Curator of the Alpha Bank Numismatic Collection, Dr. DimitraTsangari, both for the organisation of the Exhibition and forthe preparation of the bilingual catalogue. The Adminstrative Council of the Benaki Museum, moreover, owes a unique debt of gratitude to the President of the Alpha Bank, Yannis Kostopoulos, who is an unfailing source of fertile ideas and encouraging advice. (Preface by Angelos Delivorrias)